2019
DOI: 10.1111/rda.13462
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxalase 1 expression is downregulated in preimplantation blastocysts of diabetic rabbits

Abstract: In a diabetic pregnancy, an altered maternal metabolism led to increased formation of reactive α‐dicarbonyls such as glyoxal (GO) and methylglyoxal (MGO) in the reproductive organs and embryos. The enzyme glyoxalase (GLO) 1 detoxifies reactive α‐dicarbonyls thus protecting cells against malfunction or modifications of proteins by advanced glycated end products (AGEs). The aim of this study was to analyse the influence of a maternal insulin‐dependent diabetes mellitus (IDD) on GLO1 expression and activity in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…The cell line was produced by the fusion of human normal invasive extravillous cytotrophoblasts from Chorion laeve with AC1-1, an HGPRT-negative mutant of the choriocarcinoma cell line JEG-3 50 . The Ac-1M88 cells were cultured in vitro under standard conditions (humidi ed atmosphere with 5% CO 2 and 37°C) in DMEM (DMEM Glutamax F12, Gibco) with 10% FBS to 70 % con uency 51 . Then they were cultured in fresh media with/without the presence of actinomycin D at 4 nM concentration or ba lomycin A1 at 0.01 nM, 0.1 nM, 0.2 nM, 0.5 nM and 2.0 nM concentrations for 24 h. Analysis of internalisation of apoptotic cells in mouse blastocysts and the human Ac-1M88 cell line…”
Section: Human Trophoblast Cell Line Ac-1m88 Culturementioning
confidence: 99%
“…The cell line was produced by the fusion of human normal invasive extravillous cytotrophoblasts from Chorion laeve with AC1-1, an HGPRT-negative mutant of the choriocarcinoma cell line JEG-3 50 . The Ac-1M88 cells were cultured in vitro under standard conditions (humidi ed atmosphere with 5% CO 2 and 37°C) in DMEM (DMEM Glutamax F12, Gibco) with 10% FBS to 70 % con uency 51 . Then they were cultured in fresh media with/without the presence of actinomycin D at 4 nM concentration or ba lomycin A1 at 0.01 nM, 0.1 nM, 0.2 nM, 0.5 nM and 2.0 nM concentrations for 24 h. Analysis of internalisation of apoptotic cells in mouse blastocysts and the human Ac-1M88 cell line…”
Section: Human Trophoblast Cell Line Ac-1m88 Culturementioning
confidence: 99%
“…Furthermore, the GLO1 enzyme is active in rabbit blastocysts as early as during preimplantation. The GLO1 amount decreases under pathophysiological conditions of maternal diabetes mellitus in embryos [29].…”
Section: Introductionmentioning
confidence: 95%
“…For GLO1 the amplification and quantification forward (5 -ACCCCAGCACCAAGGATTTT-3 ) and reverse primer (5 -GTGCCCCAATTGTGTGTCAG-3 ) were designed based on the rabbit GLO1 gene sequence (Gene ID: 100,354,439 NCBI, accession number: XM_002714686) by Primer-BLAST. PCR products were sequenced and checked for specificity as described previously by Seeling et al [29].…”
Section: Measurement Of Mrna Levels By Quantitative Pcrmentioning
confidence: 99%
See 1 more Smart Citation
“…The enzyme glyoxalase (GLO) 1 is known to detoxify the reactive α-dicarbonyls and safeguard against modifications of proteins by advanced glycated end products (AGEs). It was shown that maternal diabetes affects the activity of GLO1 by post-translational modification due to changes in the metabolic processes in the embryos [ 15 ]. Better understanding of the potential roles of PTMs in diabetes is providing insights into the molecular mechanisms that can be targeted to develop antidiabetic drugs [ 16 ].…”
Section: Introductionmentioning
confidence: 99%